Coumarin Synthesis via Pechmann Condensation on Silica-Supported Sulfuric Acid Under Microwave Irradiation - Rad-Moghadam, Kurosh; Montazeri, Nasser (Asian Journal of Chemistry, 2010)
4-Methyl coumarin derivatives were synthesized from substituted phenols and ethyl acetoacetate via pechmann condensation under microwave and solvent-free conditions using silica-supported sulfuric acid as the catalyst.